2006
DOI: 10.1007/s10195-006-0118-9
|View full text |Cite
|
Sign up to set email alerts
|

Closed suction drainage after orthopaedic surgery: evidence versus practice

Abstract: Closed suction drainage systems are commonly used in orthopaedic surgery, particularly in joint arthroplasty. The rationale for the use of drains is a theoretical reduction of wound haematomas and infection. However the benefit of using drains after total hip or knee arthroplasty is controversial. Several reports have shown that the use of drains does not reduce infection and morbidity and is an unnecessary and potentially dangerous practice. In fact most studies highlighted that at best their use appears to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Lawson Tait's "when in doubt, drain" was countered by Halsted (1898) who argued that "no drainage at all is better than the ignorant employment of it" [11,12]. Closed suction drains are commonly used in orthopaedic surgery to avoid the accumulation of postoperative haematomas/seromas [6]. Haematomas can potentially increase tissue tension and therefore decrease tissue perfusion in the peri-wound area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lawson Tait's "when in doubt, drain" was countered by Halsted (1898) who argued that "no drainage at all is better than the ignorant employment of it" [11,12]. Closed suction drains are commonly used in orthopaedic surgery to avoid the accumulation of postoperative haematomas/seromas [6]. Haematomas can potentially increase tissue tension and therefore decrease tissue perfusion in the peri-wound area.…”
Section: Discussionmentioning
confidence: 99%
“…This could have a detrimental effect on the wound with an increased risk of wound dehiscence and infection, and poor wound healing. The routine use of closed suction drains in orthopaedics has been controversial but the practice has endured despite the availability of studies that challenge it's efficacy and identify some potential drawbacks [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The use of suction drain in upper limb surgery is still controversial. 15,16,17 Various studies reported that postoperative use of suction drain leads to retrograde migration of bacteria causing infection and there will be more chances of blood loss that will be more • A total of 120 patients were selected as per selection criteria.…”
Section: Introductionmentioning
confidence: 99%
“…It can also impair the early postoperative rehabilitation. In a recent metaanalysis, there is no clear advantage of the use of suction drains, apart from reduced need for change of dressing after total knee arthroplasty (TKA) 34. Moreover, in patients who had undergone TKA with drainage, the risk of transfusion was higher 3…”
Section: Introductionmentioning
confidence: 99%